The Factors of Affecting Labor Absorption in Java Island - Utomo, Ciptadi Prasetyo (Efficient: Indonesian Journal of Development Economics, 2022)
This study aims to determine the Gross Regional Domestic Product, the Human Development Index, the provincial minimum wage, and the unemployment rate of labor absorption in Java in 2010-2019. This study uses a panel data regression method consisting of six provinces in Java for the period 2010-2019. Tests in the study using multiple regression analysis method with analysis tools using Eviews 9. Based on these results, HDI and GRDP have a significant and positive effect. While the minimum wage and the unemployment rate have a negative and significant contribution. The suggestion that can be given is that the Government plays an important role in increasing the human development index. The government must be able to improve the quality of human resources (HR). The government must encourage and spur an increase in gross regional domestic product in every sector of the economy. The government must develop a wage policy that is mutually beneficial between workers and companies so that it does not benefit only one party. The government must create a lot of jobs, with increasing employment, unemployment will decrease, and employment will increase. Penelitian ini bertujuan untuk mengetahui Produk Domestik Regional Bruto, Indeks Pembangunan Manusia, Upah Minimum Provinsi, dan tingkat pengangguran penyerapan tenaga kerja di Pulau Jawa tahun 2010-2019. Penelitian ini menggunakan metode regresi data panel dari enam provinsi di Pulau Jawa dengan periode 2010-2019. Pengujian menggunakan metode analisis regresi berganda dengan alat analisis menggunakan Eviews 9. Berdasarkan hasil tersebut, IPM dan PDRB berpengaruh signifikan dan positif. Sedangkan upah minimu dan tingkat pengangguran memiliki kontribusi negatif dan signifikan. Saran yang dapat diberikan adalah Pemerintah berperan penting dalam meningkatkan indeks pembangunan manusia. Pemerintah harus mampu meningkatkan kualitas sumber daya manusia (SDM). Pemerintah harus mendorong dan memacu peningkatan produk domestik regional bruto di setiap sektor perekonomian. Pemerintah harus mengembangkan kebijakan pengupahan yang saling menguntungkan antara pekerja dan perusahaan sehingga tidak menguntungkan satu pihak saja. Pemerintah harus menciptakan banyak lapangan pekerjaan, dengan bertambahnya lapangan kerja, pengangguran akan berkurang, dan penyerapan tenaga kerja akan meningkat.